Developing a Policy to Support Breastfeeding in Women Who Are Hospitalized and Acutely Ill. Issue 3 (17th June 2013) - Watson, Jo; Hermann, Sue; Johnson, Billarar
Abstract Breastfeeding support is a key part of caring for childbearing women. When a woman is acutely ill, hospitalized and breastfeeding, there can be a focus on initiating or maintaining breastfeeding in challenging circumstances. This article describes the development and implementation of a policy to identify, educate and support acutely ill women and their families in reaching their breastfeeding goals. A case study highlights how we supported the initiation of breastfeeding in an adult intensive care unit. Considerations for obstetric nurses when postpartum women are hospitalized on nonobstetric units are shared.